Challenges of implementing sustainable design and construction in building projects in Kuwait - Elnakhely, Mohamed Ezzat; Alhawaj, Faisal Sadeq (Journal of engineering sciences and information technology, 2025)
The research examines the challenges of implementing sustainable design and construction in modern buildings in Kuwait and assesses the need for adopting sustainable architectural systems in the country. It also evaluates the governmental, societal, and institutional performance regarding this application. The significance of the study lies in raising awareness among stakeholders in construction projects about the importance of applying sustainable design in building projects in Kuwait. It highlights the difficulties that hinder the implementation of sustainable design and construction, as well as practical solutions to overcome them. The study follows a descriptive-analytical methodology using both quantitative and qualitative data, with a questionnaire used as a tool to collect responses. The study findings indicate a moderate level of awareness and knowledge about the benefits of applying sustainability in construction and design, averaging 48%. The absence of laws that mandate and regulate sustainable construction was identified as one of the most significant barriers, with a relative importance of 96.4%. Other major obstacles included reluctance to change traditional construction methods (95.6%), lack of incentives for sustainability application (92.6%), and absence of institutional support for implementation (89.4%). Additionally, there was limited knowledge about integrating sustainability into design and construction, its cost impact on projects, and post-construction maintenance methods, with a relative importance of 86.4%. The study recommends increasing public awareness about the benefits of sustainable design and construction, integrating sustainability principles into education and training, and providing governmental and institutional support to encourage its adoption. It also suggests offering incentives for projects that comply with sustainability standards, mandating institutions to assess the environmental impact of projects, developing environmental legislation, and creating a sustainability classification system suitable for Kuwait. Furthermore, it proposes establishing a geographic database for sustainable projects, developing a detailed guide on applying sustainability at different project stages, and adopting participatory methodologies to exchange expertise in sustainability. Additional recommendations include requiring new buildings to install solar energy systems covering at least 30% of their energy needs.